A Management To Strengthening Islamic Boarding Schools’ Quality Graduates - Nurhayati, Siti; Wasliman, Iim; Sauri, Sofyan; Arifin, Daeng (International Journal of Educational Research & Social Sciences, 2022)
The research aims to explore and observe a management to strengthening Islamic Boarding Schools Graduates in Indonesian context. This research uses a qualitative approach because this research aims to describe and analyze the process of strengthening graduates in perspective of management. Various data collection techniques are used including: observation, interview, documentation study, literature studies and triangulation. The result shows the planning, implementation, evaluation, and follow-up stage supported to realize academic and non-academic graduates’ quality, as well as to develop cultural values and character that can be implemented in everyday life but still not able to be done to the fullest. At the planning stage, it can be interpreted that the program planning has been prepared oriented to the quality that can be realized optimally. The implementation in improving graduates quality conducted in both Islamic schools, includes: Curriculum Development, Learning Activities, Educator and Educational Personnel Competency Improvement Activities, Student and Extracurricular Activities, Facilities Management Activities and Infrastructure, Financing Management, Partnership Activities and society’s role. In the supervision and evaluation part, is done to ensure management to strengthen the graduates is in accordance with planning. To sum up, the management has not been able to be done optimally, because it cannot carry out the face-to-face learning process followed by all learners, such as normal condition so that many obstacles faced by teachers and by learners.